Analisis Penerapan Job Order Costing pada UKM Percetakan - Wahyuni, Dian (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
Printing PT. Cempaka Mas Solutions or Print Art is a business unit engaged in printing production. Printing business unit PT. Cempaka Mas Solutions or Print Art has not calculated the cost of production correctly as the basis for determining the selling price. The purpose of this research is to apply the job order costing method to the selling price at PT. Cempaka Mas Solutions or Print Art. This research uses a quantitative descriptive approach which is carried out in the printing business unit of PT. Cempaka Mas Solutions or Print Art. This research is a descriptive type, which is to draw samples and show an empirical picture of reality according to what is happening in the field. Data obtained from direct observation in the printing business unit of PT. Cempaka Mas Solutions or Print Art and then applied to the calculation of the cost of production using the job order costing method to determine the selling price. After being identified and grouped, the calculation of the cost of goods manufactured is carried out using job order costing on Calendar orders, which consume more raw materials and labor than invitations and brochures, as well as the best type of paper. In the process of printing brochures, invitations and calendars using the same machine, the difference is only in direct working hours depending on the number of orders requested and final completion.